Transforming Agrifood Systems in South Asia(TAFSSA) Newsletter June 2024 - Krupnik, Timothy J.; Menon, Purnima (International Maize and Wheat Improvement Center, 2024)
TAFSSA collaborates hundreds of national and regional research, extension, private sector, and development partners in Bangladesh, India, Nepal, and Pakistan. The Initiative actively supports and integrates CGIAR's thematic research initiatives in Genetic Innovations, Resilient Agrifood Systems (RAFS), and Systems Transformation (ST) science groups to achieve improved synergy, coherence, and impact from CGIAR’s research efforts in South Asia. This alignment extends to pertinent non-pooled research and development projects that – in an efficient portfolio context that achieves economies of scale – generate highly pertinent scientific outputs and outcomes. TAFSSA facilitates capacity-sharing efforts and is a catalyst for innovation development and scaling across CGIAR's five Impact Areas, including: Nutrition, Health, and Food Security; Poverty Reduction, Livelihoods, and Jobs; Gender Equality, Youth, and Social Inclusion; Climate Adaptation and Mitigation; Environmental Health and Biodiversity.